REPRESENTASI KESETARAAN PERAN SUAMI DAN ISTRI DALAM FILM CHELOVEK KOTORIY UDIVIL VESKH/ PRIA YANG MENGEJUTKAN SEMUA ORANG - Sekara, Amanda Herawaty; Widyastuti, Thera (UI Scholars Hub, 2026)
As one of the most popular forms of cultural production, film does not merely function as entertainment for society but also serves as a medium for highlighting social issues that have occurred or are currently unfolding within it. One Russian film that raises such social issues is Chelovek, kotoryj Udivil Vsekh (The Man Who Surprised Everyone), which implicitly addresses gender equality in modern Russian society. This study examines the representation of equality between women and men within the domestic sphere and how it relates to social realities in contemporary Russia. The theories of gender equilibrium and feminism, along with character analysis, are employed to analyze the issues in the lives of Egor and Natalya. The findings demonstrate that the idea of equality in spousal roles can be conveyed, with the hope of contributing to a shift in the reality of household life in Russia toward a new condition in which husbands and wives hold equal positions within the family.